Penceritaan peristiwa Isra' dan Mi'raj oleh Sheikh Daud al-Pattani. Kajian teks dan pengaruhnya dalam masyarakat Islam di Pattani, Thailand / Saref Masae - Saref , Masae (2016)
The book Kifayah Al Muhtaj written by Shiekh Daud AlFatani is one of the books written in jawi script regarding the story of Isra and Mikraj. Sheikh Daud completed writing this book in the year 1224H. The purpose of this study is to study the event of Isra and Mikraj focusing on the book, detailing the study of Isra and Mikraj. It is also to find out the response of the book in the understanding Isra and Mikraj. This study is to evaluate the historical source of this book.The method of collecting the data and analysing the data is through the usage of history, gathered in the context of history. The data for analysis used the inductive method in order to define the data specifically to be clear and precise, while deductive method is used for solutions and conclusions. Comparative method was also used for comparison. Results from the study showed that the book Kifayah Al Muhtaj is still in use for reference for Isra and Mikraj within the Patani Islamic community. This is because in the eyes of the Patani community, the book is any flaws and mistakes. Lastly, the study suggests further studies on other books written and left by Sheikh Daud which need explanations in this modern time .